Pediatric Intestinal Rehabilitation and Transplantation Registry: Initial Report from a European Collaborative Registry - Totonelli, Giorgia; Tambucci, Roberto; Boscarelli, Alessandro; Hermans, Dominique; Dall'Oglio, Luigi; Diamanti, Antonella; d'Aische, Aloys du Bois; Pakarinen, Mikko; Reding, Raymond; Morini, Francesco; Bagolan, Pietro; Fusaro, Fabio (European Journal of Pediatric Surgery, 2018)
Introduction Short bowel syndrome (SBS) is the main cause of intestinal failure (IF) in the pediatric population. To promote the standardization of care of these patients, the registry of Pediatric Intestinal Rehabilitation and Transplantation (PIRAT) has been established. The aim of this study is to describe patients with IF using PIRAT database.Materials and Methods Data from two tertiary care European referral Centers registered in PIRAT (https://www.studeon.eu/pirat) were analyzed (1994–2015). Neonatal SBS-related IF was defined as need for parenteral nutrition (PN) to sustain life and growth for more than 75 days, after extensive bowel resection during neonatal period. Data included patient demographics, disease at birth, residual small intestine, and intestinal autonomy (PN on/off).Results In this study, 114 children with SBS-related IF were identified (male 60%). Median gestational age was 35.3 weeks (interquartile range [IQR]: 33.0–38.0); median birth weight was 2,440 g (IQR: 1,700–2,990). The main causes of SBS were intestinal atresia in 31 (27%), midgut volvulus in 29 (25%), necrotizing enterocolitis in 23 (20%), and gastroschisis in 12 (11%). Nine (7.9%) patients died on PN (six sepsis, two IF-associated liver disease, and one multiorgan failure). Median residual small bowel length was 46 cm (IQR: 13.0–92.5). Ileocecal valve was resected in 48 patients (42%). Intestinal autonomy was achieved in 68% patients.Conclusion We present the web-based registry PIRAT and the first results of patients with IF registered from two European Centers. PIRAT could give the opportunity to create a dedicated international network (IF-net) to standardize, improve, and spread the therapeutic paths for the rare and heterogeneous condition of SBS-related IF.
Keywords: intestinal failure; short bowel syndrome; parenteral nutrition; registry; intestinal transplantation